Ideology in the language of judges : how judges practice law, politics, and courtroom control - Philips, Susan Urmston (Oxford studies in anthropological linguistics, 1998)
Studying the language of judges in courtrooms, the author of this text demonstrates that they are not impartial arbiters of due process, but are influenced by their own politico-ideological stance and interpretation of the law.